Evaluation of a home-based parenting support programme-Parenting Young Children-For parents with intellectual and developmental disabilities when there is a risk for neglect: Study protocol for a multi-centre study. - Marie Holmefur; Tommie Forslund; Eva Randell; Birgitta Wennberg; Maria Ayoub; Lena Almqvist; Karin Fängström; Gunnel Janeslätt; Thomas Strandberg (PLoS ONE)
Introduction Parents with intellectual and developmental disabilities (IDDs) often need parenting support, but there are few evidence-based programmes adapted to their cognitive needs. Parenting Young Children (PYC), a home-based programme for parents with IDDs, is perceived as beneficial by parents and practitioners, but it is unclear if PYC improves parenting. The purpose of the proposed mixed-methods study is therefore to evaluate the PYC programme for improved parenting in parents with IDDs. Methods and analysis The quantitative evaluation will have a multi-centre, pretest-posttest study design and include parents with IDDs (children aged 0-9) in need of adapted parenting support. Goal-attainment in parenting skills, parental self-efficacy and child mental health will be measured outcomes. Interviews will be used to explore the perspectives of parents and children on PYC. Ethics and dissemination Particpation is based on informed consent from parents and guardians of the participating children. Ethical approval was granted by the Swedish Ethical Review Authority.